10 - Les mesures de réajustement de l'économie ivoirienne face a la crise économique mondiale: Leurs résultats et leurs implications sociales* - Bamba MOUSSA, (Africa Development, 1985)
The entire International Community is seriously preoccupied by the increasing indebtness of Third-World countries. As a result of the enormous proportion it has taken, it now dominates the discussions on economy and finance and seriously jeopardises the efforts of young nations in social and economic development. The Ivory Coast has been particularly hit by the hardship. After a long period of economic growth made possible by favourable price offered for the main export products — coffee and cocoa — the Ivory Coast drew up an impressive public investment programme whose components have not always been fully evaluated. However, from 1979 to1982, the country faced one of the most adverse situations in terms of its foreign exchange, its trade balance and balance of payments were seriously affected and public income dwindled considerably. Therefore, the Ivory Coast, like other African countries, resorted to the IMF and signed an agreement with the Fund in February 1981. Accordingly it received two structural adjustment loans which both aimed at improving the economy in agriculture, industry and mines, and housing. In agriculture, efforts were geared to defining and applying new policies on prices, subsidies and trading; restructuring agricultural enter prises in the parastatal sector by improving their effectiveness and viability; defining and applying a new strategy for rural development towards moder nisation, diversification of agricultural production and especially at promo ting food production witnin the framework of a long-term self-sufficiency in food. In industry and mines, solutions were to be found to the following problems: diminution in the competitivity of enterprises, discrimination in tne system of incentives, weak integration of industries and weakness of the policy of the promotion of local industry. As far as housing is concerned, the issues of offer of land, housing aid in rural areas, mobilisation of savings and financing of housing as weu as creation of a structure of animation and coordination were to be consi dered again. The Ivorian case brings into question the role international financial institutions play in the so-called structural adjustment programmes. The point is that the experts of these institutions never take into consideration the sociological realities of the countries they are supposed to advise. They simply apply the same remedy indiscriminately, regardless of the differences between the countries ana at the risk of general discontent with unforeseable consequences.